DC voltage-based virtual synchronous generator scheme for eliminating circulating power of two-stage grid-tied converters - Hao, Tianqu; Zhu, Jun; Gao, Feng; Zhao, Xingjian (Frontiers in Energy Research, 2023)
Virtual synchronous generators (VSGs) powered by renewable energy sources prefer to have energy storage (ESs) attached to the DC-link with DC-DC converters, emulating the inertia and smoothing the intermittency of renewable generations. This paper proposes a new VSG method for a two-stage converter to eliminate the circulating power among inverters meanwhile with the identical external characteristics of traditional VSG. In particular, the proposed VSG method uses the inverter, ES converter, and DC capacitor together to implement the swing equation. Meanwhile, the method can still achieve strong similarities with synchronous generators in terms of physical structure, control, and mathematical model. Therefore, the stable operation of the proposed VSG is easy to evaluate by the well-developed traditional power system theory. Moreover, the method is developed to be capable of eliminating circulating power among paralleled VSGs. Simulation and experimental results have also verified the effectiveness of the proposed method.